STRATEGI KOMUNIKASI DALAM PROSES PROMOSI PENYALURAN KERJA PADA SMK MITRA INDUSTRI MM2100 - Arifin, Ahmad Nur; Poerana, Ana Fitriana; Kusumaningrum, Rastri (Linimasa : Jurnal Ilmu Komunikasi, 2021)
Vocational High school is the institution that prepares students to work immediately after graduation. However, not all of vocational school graduates can immediately work, even many of them are unemployed as presented in the data of BPS 2020. The study is unique in that it endeavors to review communication strategies used to promote human resources rather than products like most other studies. The focus of this research is onn how to communication strategies used by Mitra Industri MM2100 VHS in his employment distribution campaign. In the study, the concept of the stage of communication strategy presented by Hafied Cangara and elaboration likelihood model according to Petty and Cacioppo. The study employed qualitative methods with descriptive as well as data analysis models Miles and Huberman. The results obtained in this study are communication strategies that are implemented by implementing communication strategies the stages of research, planning, execution, evaluation and reporting. Promotional activities also have contributing factors and inhibitors. As well as the elaborate route that is run by the promotional target is the central route.